An assessment of the Ca-V-O system. (March 2017) - Yang, Yang; Mao, Huahai; Selleby, Malin
Abstract: The Ca-V-O system is studied with an emphasis on the following oxide sub-systems: CaO-V2 O5, CaO-V2 O3, V2 O5 -CaV2 O5 and CaO-V2 O5 -VO2 . The aim of the present assessment is to obtain a thermodynamic description of the Ca-V-O system. The compound energy formalism was used to describe the liquid by applying the ionic two-sublattice model and the β-bronze phase Cax V2 O5 (0.17≤x≤0.33) using a three-sublattice model. Phase equilibria and thermodynamic properties were critically evaluated using the CALPHAD approach and a consistent set of thermodynamic model parameters was obtained. Satisfactory agreement between calculated and experimental values is achieved. Highlights: Emphasis on the sub-systems: CaO-V2 O5, CaO-V2 O3, V2 O5 -CaV2 O5 and CaO-V2 O5 -VO2 . A self-consistent thermodynamic dataset of the Ca-V-O system is obtained. The liquid phase is described using the ionic two-sublattice model. The β-bronze phase Cax V2 O5 (0.17≤x≤0.33) is modeled using a three-sublattice model. The isothermal sections of CaO-V2 O5 -V2 O4 at 873 and 923 K have been reproduced.